2010
DOI: 10.1128/jb.01564-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Substrates of the StkP Ser/Thr Protein Kinase in Streptococcus pneumoniae

Abstract: Monitoring the external environment and responding to its changes are essential for the survival of all living organisms. The transmission of extracellular signals in prokaryotes is mediated mainly by twocomponent systems. In addition, genomic analyses have revealed that many bacteria contain eukaryotictype Ser/Thr protein kinases. The human pathogen Streptococcus pneumoniae encodes 13 two-component systems and has a single copy of a eukaryotic-like Ser/Thr protein kinase gene designated stkP. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 56 publications
11
74
0
Order By: Relevance
“…4C). When norfloxacin was added, a slightly reduced protein phosphorylation pattern was observed, perhaps caused by an arrested growth in the presence of this antibiotic, consistent with previous reports (33). Strikingly, we observed hyperphosphorylation in the presence of ampicillin, and a previously faintly phosphorylated band (26), representing an as yet unknown protein, became robustly phosphorylated (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…4C). When norfloxacin was added, a slightly reduced protein phosphorylation pattern was observed, perhaps caused by an arrested growth in the presence of this antibiotic, consistent with previous reports (33). Strikingly, we observed hyperphosphorylation in the presence of ampicillin, and a previously faintly phosphorylated band (26), representing an as yet unknown protein, became robustly phosphorylated (Fig.…”
Section: Resultssupporting
confidence: 92%
“…To test this notion, we examined the in vivo Thr protein phosphorylation profile of cells incubated with vancomycin or ampicillin. A phosphoprotein pattern was observed that included the StkP substrates DivIVA and Spr0334, as previously identified (33). In line with the localization results, protein phosphorylation was reduced significantly by adding vancomycin (Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations